ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN (GREEN ACCOUNTING) PADA PENGELOLAAN LIMBAH DI RSUD RADEN MATTAHER - Flora, Madya; Rafidah, Rafidah; Tanjung, Ferri Saputra (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to analyze the implementation of environmental accounting (green accounting) in waste management at RSUD Raden Mattaher Jambi. A qualitative descriptive method was used, with data collected through interviews, observations, and documentation. The results indicate that the hospital has initiated basic steps in applying environmental accounting, such as waste segregation, recording operational costs, and collaborating with third parties for hazardous waste (B3) management. However, environmental costs are not yet classified separately in the financial reports, and there is no integrated reporting system that reflects all categories of environmental costs as outlined by Hansen and Mowen. The main obstacles include limited technology, lack of internal regulations, and insufficient staff training. Despite these challenges, RSUD Raden Mattaher has shown initial commitment through the preparation of work and budget plans (RKA), internal reporting, and development of Standard Operating Procedures (SOP). This study concludes that the implementation of environmental accounting at RSUD Raden Mattaher Jambi still needs to be strengthened to achieve accountable, transparent, and sustainable waste management